Length-based stock assessment in small-scale multi-gear fisheries: insights from a European hotspot (NW Spain) - Daniel García-García; Marta Cousido-Rocha; Rafael Bañón; José Manuel Campelos; Fernando Quintero; Asunción Gancedo; Fabio Lamas; Alberto Otero; Angel Rodríguez; Alexandre Alonso-Fernández (Reviews in Fish Biology and Fisheries, 2026)

In vitro evaluation of antimicrobial activity of Lactic Acid Bacteria (LAB) isolated from Buffalo milk against most common pathogenic and spoilage food bacteria - Marika Di Paolo; Valeria Vuoso; Alexandre Lamas; Rosa Luisa Ambrosio; Carlos Manuel Franco; Aniello Anastasio; Raffaele Marrone (International Dairy Journal, 2026)

Development of fluorescence and colorimetric LAMP-based assays for rapid and sensitive detection of toxigenic Bacillus cereus group strains in plant-based products - Marta Bisaschi; Alessandra Fontana; Maria Luisa Callegari; Antonio Del Casale; Lorenzo Morelli; Alexandre Lamas; Marta Prado; Vania Patrone (Food Control, 2026)

Energy–environmental nexus in green hydrogen-assisted conversion of second-crop canola to sustainable aviation fuel: Toward low-carbon bioenergy systems - Giulia Cruz Lamas; Alexandre Nunes Cardoso; Priscila Seixas Sabaini; Sandra M. Luz; Maria dos Reis Santos Borges; Tainara da S. Costa; Thiago da Silva Gonzales; Marilia Ieda da Silveira Folegatti Matsuura; Bruno Galveas Laviola; Thiago O. Rodrigues; Patrick Rousset; Edgar A. Silveira (Biomass and Bioenergy, 2026)

Unveiling the metabolic impact of recombinant growth hormone in dairy cows: an integrated metabolomics analysis of milk and urine - Axel Raux; Yann Guitton; Patricia Regal; Alexandre Lamas; Elena Bozzetta; Marzia Pezzolato; Bruno Le Bizec; Alessandro Benedetto; Gaud Dervilly (Food Additives & Contaminants: Part A, 2026)

The role of time to positive blood cultures in enhancing the predictive capability of DENOVA score for diagnosing infective endocarditis in patients with Enterococcus faecalis bacteremia - M Teresa Pérez-Rodríguez; Olalla Lima; Martín Garrido; Anniris Rincón; Lucía Martínez-Lamas; Alexandre Pérez-González; Alejandro Araújo; Antía Amoedo; Adrián Sousa; Ana López; Xurxo Cabrera; Martín Rubianes (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Assessment of the presence of Acinetobacter spp. resistant to β-lactams in commercial ready-to-eat salad samples - Ana Costa-Ribeiro; Sarah Azinheiro; Sandra Mota; Marta Prado; Alexandre Lamas; Alejandro Garrido-Maestu (Food Microbiology, 2024)

Multivariate modeling and optimization of the reverse cationic flotation process of iron ore using depressant-modified starch - Matheus Furlan Pinheiro; José Izaquiel Santos da Silva; Clarissa Nascimento de Oliveira; Edilailsa Januário de Melo; Alexandre Boscaro França; Gisella Lamas Samanamud; Mateus de Souza Amaral; Renata Carolina Zanetti Lofrano; Luzia Lima Rezende Naves; Fabiano Luiz Naves (Minerals Engineering, 2024)

Phage amplification coupled with loop-mediated isothermal amplification (PA-LAMP) for same-day detection of viable Salmonella Enteritidis in raw poultry meat - Alexandre Lamas; Sílvio B. Santos; Marta Prado; Alejandro Garrido-Maestu (Food Microbiology, 2023)

Evaluation of Covalent Organic Frameworks for the low-cost, rapid detection of Shiga Toxin-producing Escherichia coli in ready-to-eat salads - Ana Costa-Ribeiro; Sarah Azinheiro; Soraia P.S. Fernandes; Alexandre Lamas; Marta Prado; Laura M. Salonen; Alejandro Garrido-Maestu (Analytica Chimica Acta, 2023)

The interaction between liver cirrhosis, infection by Streptococcus bovis, and colon cancer - Juan Corredoira; Enrique Miguez; Lara María Mateo; Ricardo Fernández-Rodríguez; José Francisco García-Rodríguez; Alexandre Pérez-González; Ana Sanjurjo; María Victoria Pulian; Blanca Ayuso-García; M. Serrano; M. J. Jove; P. Alonso; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Modeling and optimization of the pyrolysis oil production process from polypropylene for the production of aviation kerosene - Heraclito Alexandre dos Santos; Igor José Boggione Santos; Cristiane Medina Finzi Quintão; Vagner Fernandes Knupp; Renata Carolina Zanetti Lofrano; Eliane Cristina de Oliveira; Gisella Lamas Samanamud; Mateus de Souza Amaral; Alexandre Boscaro França; Mariana Arruda Pereira; Matheus Teixeira Araújo Silva; Carla Cristina Almeida Loures; et al. (Clean Technologies and Environmental Policy, 2023)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Optimization of treating phenol from wastewater through the TiO2-catalyzed advanced oxidation process and response surface methodology - Camila Oliveira Guimarães; Alexandre Boscaro França; Gisella Rossana Lamas Samanamud; Eduardo Prado Baston; Renata Carolina Zanetti Lofrano; Carla Cristina Almeida Loures; Luzia Lima Rezende Naves; Fabiano Luiz Naves (Environmental Monitoring and Assessment, 2019)

Evaluation of the effectiveness of red mud-supported catalysts in combination with ozone and TiO2 in the treatment of solution containing benzene, toluene, and xylene - Bernardo Alves de Lima; Pedro Paulo Rocha de Castro; Alexandre Boscaro França; Eduardo Prado Baston; Renata Carolina Zanetti Lofrano; Gisella Rossana Lamas Samanamud; Carla Cristina Almeida Loures; Luzia Lima Rezende Naves; Fabiano Luiz Naves (Environmental Monitoring and Assessment, 2018)

Normal boundary intersection applied as multivariate and multiobjective optimization in the treatment of amoxicillin synthetic solution - Deberton Moura; Vithor Barcelos; Gisella Rossana Lamas Samanamud; Alexandre Boscaro França; Renata Lofrano; Carla Cristina Almeida Loures; Luzia Lima Rezende Naves; Mateus Souza Amaral; Fabiano Luiz Naves (Environmental Monitoring and Assessment, 2018)

Food patterns and nutritional assessment in Galician university students - José J. Porto-Arias; Tania Lorenzo; Alexandre Lamas; Patricia Regal; Alejandra Cardelle-Cobas; Alberto Cepeda (Journal of Physiology and Biochemistry, 2018)

Reproductive ecology of Brazilian freshwater fishes - Alexandre Lima Godinho; Ivana Reis Lamas; Hugo Pereira Godinho (Environmental Biology of Fishes, 2010)